Gambaran Personal Hygiene Pada Anak Berkebutuhan Khusus Dengan Tunagrahita di SLB Kota Surakarta - Putri Syafira Salsabilla; Siti Fatmawati (Lembaga Pengembangan Kinerja Dosen, 2024)
Children with special needs with tunagrahita are children who have physical, mental and behavioural limitations, this causes difficulties in performing personal hygiene in everyday life. In Surakarta City, the prevalence of tunagrahita in 2023 shows that there are 1,118 children with special needs. Objective: To determine the description of personal hygiene in children with special needs with tunagrahita. Methods: This type of research uses descriptive quantitative. The sampling technique used total sampling with a sample size of 153 respondents. Results: This study shows that based on personal hygiene the majority of respondents have less ability as many as (42.5%) 65 respondents. Conclusion: The description of personal hygiene skills in children with special needs with tunagrahita in the category of less.